Nilai nutrisi ekstrak buah nipah dan pengaruhnya terhadap glucose transporter-2 (GLUT-2) pada tikus yang diinduksi STZ - Fitri, Yulia; Wagustina, Silvia; Husna, Fauzul; Suryana, Suryana; Zakiah, Noni; Sastri, Sastri (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: The nutritional content of nipah fruit such as zinc and fiber plays an important role in regulating blood sugar levels in diabetes patients (DM). One way to increase the concentration of nutritional value and bioactive substances in palm fruit is to extract it. Active compounds such as tannins, flavonoids, polysaccharides, saponins, and terpenoids in palm fruit extract can inhibit the activity of amylase and glucosidase enzymes, which are mediated by Glucose Transporter-2 (GLUT-2) so that they affect controlling blood sugar levels. GLUT-2 is a protein that plays a role in transporting glucose from outside to inside cells, so it plays an essential role in maintaining balanced blood sugar levels.Objective: This research aims to examine the nutrients in palm fruit extract and its effect on Glucose transporter-2 (GLUT-2) in STZ-induced  in rats.Method: This study is experimental research using experimental laboratory methods carried out in the FKH USK laboratory in June 2022. Making nipah fruit extract is carried out by maceration using 95% ethanol. Carbohydrate, protein, fat, zinc, and Fe levels were analyzed using the Luff Schoorl, Kjeldahl, Soxhletasi, and AAS test method. Testing for water content and crude fibre uses a gravimetric test. Twenty-five rat samples were divided into four groups and induced with STZ 40 mg/kg BW. Checking blood sugar levels is needed to see hyperglycemic conditions in rats. GLUT-2 measurement after administering nipah extract for one month using the ELISA technique. The data obtained were analyzed by an ANOVA test.Results: Based on the results, it was found that fruit extract contained 15,79% carbohydrates, 7,04% protein, 6,02% fat, 0,0327% zinc, water content 24,05% and crude fibre 0,36%. The average GLUT-2 level in the control group was 7,24 ± 1,35 ng/ml, the DM group was 6,75 ± 0,81 ng/ml, the DM+extract group was 6,84 ± 0,56 ng/ml, the DM+metformin group was 7,34 ± 0,86ng/ml, and the DM+extract+metformin group was 6,93± 1,01 ng/ml.Conclusion: Nipah fruit extract contains carbohydrates, protein, fat and zinc. Administration of palm fruit extract for one month did not significantly effect on GLUT-2 in various groups of rats (0,83).